An Investigation of Virulence Genes of Staphylococcus aureus in Autologous Vaccines Against Sheep Mastitis - Erminia Sezzi; Rita Fanelli; Deborah Gobbi; Paolo Scandurra; Valerio Mannucci; Isabella Usai; Giovanni Ragionieri; Ziad Mezher; Gianluca Fichi (Animals)
Staphylococcus aureus is well known to be the primary causal agent of clinical or subclinical mastitis in dairy sheep. The production of virulence factors allows S. aureus strains to cause mastitis. In the present study, 96 strains isolated from dairy sheep farms used for the production of autologous vaccines were tested for enterotoxin and hemolysin genes by PCR. In addition, 14 strains isolated from half udders of ewes with subclinical mastitis belonging to a single farm were also tested for the same genes. The phylogenetic trees were constructed, and spatial analysis was performed. Overall, 20 gene patterns were identified, but 43.64% of the tested strains showed the same profile (sec+, sel+, hla+, hld+, hlgAC+). Considering only the enterotoxin genes, four profiles were identified while the evaluation of the hemolysin genes revealed the presence of 12 gene patterns. In the farm with subclinical mastitis, six gene profiles were found. Spatial analysis of the isolated strains and their virulence genes did not show a specific pattern. The present study highlights the importance of identifying and analyzing virulence genes of S. aureus strains involved in dairy sheep mastitis, and the presence of different strains in the same farm.